Analysis of the Integration of Digital Accounting Systems and Digital Payment Systems in Improving the Quality of Financial Reporting among MSMEs: A Qualitative Study - Thresia Elaine Aritonang; Riyana Eprilia Putri; Novi Dwi Setiawati; Tyas Pambudi Raharjo (The Future of Education Journal, 2026)
This study aims to analyze how the integration of digital accounting systems and digital payment systems improves the quality of financial reporting among micro, small, and medium-sized enterprises (MSMEs) based on the qualitative characteristics prescribed by the Indonesian Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The study employed a qualitative approach using a library research method. Data were obtained from official publications of Bank Indonesia, the Indonesian Institute of Accountants (IAI), the Ministry of Micro, Small, and Medium Enterprises, Statistics Indonesia (BPS), the Financial Services Authority (OJK), as well as national and international scholarly publications published between 2023 and 2026. Data were analyzed through the stages of data reduction, categorization, data presentation, synthesis, and conclusion drawing. The findings indicate that integrating digital accounting applications, such as Accurate, Mekari Jurnal, BukuKas, Majoo, and Paper.id, with digital payment systems, including QRIS, e-wallets, and mobile banking, enables the automation of transaction recording, improves data accuracy, accelerates financial reconciliation, and enhances the transparency and accountability of financial reporting. This integration also supports the fulfillment of the qualitative characteristics of financial statements relevance, faithful representation, comparability, understandability, and timeliness as required by SAK EMKM. This study contributes by presenting a conceptual framework that integrates digital accounting systems and digital payment systems, providing valuable insights for MSME owners, technology providers, and policymakers in supporting the digital transformation of MSME financial management in Indonesia.